Gender Differences in Theory of Mind, Empathic Understanding, and Moral Reasoning in an Offending and a Matched Non-Offending Population - Spenser, Karin A. (International journal of offender therapy and comparative criminology, 2022)
Previous research suggests that a lack of pro-social skills is characteristic of an offending personality. Two hundred male and female offenders and matched controls completed measures to assess: Theory of Mind, empathic understanding, and moral reasoning. Significant differences between the offenders and the control group, as well as between the male and female participants, were detected in theory of mind, empathic understanding and moral reasoning with offenders scoring lower than the control group, and with males scoring lower than females on most tests. The ability to assess Theory of Mind, empathic understanding, and moral reasoning, and subsequently to identify reduced ability, is not only useful for researchers but will also allow practitioners to tailor existing (or develop new) interventions specific to the needs of individuals. This could be particularly useful in terms of recidivism when applied to those involved in anti-social or offending behavior.